How do memories of having been parented relate to the parenting-experience of fathers in treatment for intimate partner violence?: a phenomenological analysis - Mohaupt, Henning (Journal of family violence, 2021)
Few studies have examined how men who use intimate partner violence (IPV) experience being a parent. This study describes how Norwegian men in treatment for IPV reflect upon the impact of their childhood experiences on their fathering. We interviewed 11 men in treatment for IPV regarding their fathering experience, and their memories of having been parented. We performed a descriptive phenomenological analysis of the data. We identified two superordinate themes that described the participants’ fathering experience: being a benign versus being a detrimental force in the child’s life and having the intention of not repeating and the actual repetition of harmful parenting. The participants described being conflicted regarding being potentially damaging for their child’s development. They generally described a lack of stable positive relationships, both early in life and in the present. Partner-violent men’s meaning making of their fathering seems to be influenced by their early-life experiences with their parents in several problematic ways. Fathers who use IPV may both accept and reject that they have been harmed by the parenting they received as children. Similarly, they may both acknowledge and discard that their use of violence harms their children. We suggest that therapy should explore these themes and their consequences for the father - child relationship.